ANALISIS PENGARUH INFORMASI GADAI, KUALITAS JASA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PEGADAIAN SYARIAH CABANG KUALA SIMPANG KABUPATEN ACEH TAMIANG - Nurlatifah Nurlatifah (IAIN Langsa, 2017)
This research was aimed to find out empirical evidences of pawn information and service quality and care quality effecting on customer’s satisfaction in Syari- ah pawnshops branch Kuala Simpang Aceh Tamiang Regency. Analysis tool was used is multiple linear regression. The populations in this research are custom- ers of Syariah pawnshop branch Kuala Simpang Aceh Tamiang Regency with 100 customers as sample. Data conducted by using questionnaire technique. The results showed partially that pawn information and service quality and care quality have real effect towards customer’s satisfaction. Pawn information has regression coefficient about 0.054, service quality has regression coefficient about 0.259, care quality has regression coefficient about 0.176, which gives the meaning that pawn information and service quality and care quality improved will increase in the value of customer satisfaction. The research also shows that simultaneously pawn information and service quality and care quality are sig- nificantly effecting and explaining customer satisfaction at Syariah pawnshops branch Kuala Simpang Aceh Tamiang Regency about 41.3%. Among all variables which are examined, service quality is the most dominant variable.